2016
DOI: 10.1200/jco.2016.34.3_suppl.234
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life (HRQL) in Hodgkin lymphoma (HL): A systematic review (SR).

Abstract: 234 Background: AlthoughHL is highly curable with well-established treatment regimens, the impact on patients' HRQL from diagnosis through survivorship is unclear. This SR aimed to: (1) describe the literature on HRQL in HL, (2) assess the quality of these studies and (3) identify gaps for future research. Methods: We performed a PRISMA-guided SR on HRQL in HL patients. Identified articles were double-screened and data extracted; quality was evaluated using a 6-point scale adapted from published HRQL SR. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Currently, the US Food and Drug Administration and European Medicines Agency, recommend PROs as a prioritized treatment outcome (26, 27). Indeed, the added value of including PROs in clinical trials of HL patients has previously been reported (28)(29)(30). Data derived from PRO assessment can provide the patient-level impact of regimens on event-free survival, overall survival, and tolerability of the acute as well as the long-term effects of treatment.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Currently, the US Food and Drug Administration and European Medicines Agency, recommend PROs as a prioritized treatment outcome (26, 27). Indeed, the added value of including PROs in clinical trials of HL patients has previously been reported (28)(29)(30). Data derived from PRO assessment can provide the patient-level impact of regimens on event-free survival, overall survival, and tolerability of the acute as well as the long-term effects of treatment.…”
Section: Introductionmentioning
confidence: 98%
“…It is also important to note that improvement in QoL is included in the European Society of Medical Oncology Magnitude of Clinical Benefit Scale to determine the "value" of novel therapeutic options in cancer (31-33). Several systematic reviews on the use of PROs in clinical trials in the HL setting have previously been published (29,30,34). However, for trials involving HL patients, it still is unclear as to which PRO instruments are used, frequency of their use, and whether their results are consistently reported.…”
Section: Introductionmentioning
confidence: 99%